ALTERNATIVES PRODUCTS IN THE IN VITRO DISINFESTATION IN ROOTSTOCK EXPLANTS DUKE-7 AND IDENTIFICATION OF ENDOPHYTE MICROORGANISMS - Sandra Luz Castro Garibay; Angel Villegas Monter; Gabriel Alejandro Hernández Nava; Coral Mendoza Ramos; Mercedes Martínez Villagómez; Claudia Reyes Quiroz; Sergio Aranda Ocampo (Tropical and Subtropical Agroecosystems, 2023)
Background. The vegetative material for in vitro establishment of avocado explants is from the field, for this reason, the proportion of contamination, oxidation and mortality of explants is elevated, therefore we are looking for alternatives to decreased. Objective. To evaluate concentrations of alternative products for disinfestation in avocado explants cv Duke 7, and decrease oxidation with the addition of L-cysteine in the in vitro establishment. Methodology. The products used were: peroxyacetic acid (AP), chlorine dioxide (DC), and quaternary ammonium salts (ACS), in three concentrations. 54 explants were used in each treatment, and placed in culture medium for establishment, evaluating contamination (%) and oxidation (%). Two weeks later, 50% of viable explants from each treatment were immersed in L-cysteine (100 mgL-1) and placed in a culture medium for multiplication, the rest was placed a in multiplication medium containing L-cysteine; only oxidation was evaluated (%). Contaminated explants were isolated, identified, and characterized fungi and bacteria. Results. The best results of the disinfestation were with ACS with 3.7% contamination, without oxidation. Regarding the use of L-cysteine (100 mgL-1), the lowest percentage of oxidation (47%) was obtained when immersed in a cysteine solution. Three genera of fungi were identified: Aspergillus (3), Penicillium (1) and Cladosporium (1), and Agrobacterium as a bacterium. Implications. With the proposed methodology, we can continue with the following stages of in vitro culture, to establish methodologies for budding, growth, and rooting of avocado clonal rootstocks. Conclusions. The use of ACS and cysteine in solution reduces both contamination and oxidation of explants, but it is necessary to modify concentrations and exposure times in the disinfestation protocol, in addition to identifying even the genus the microorganisms found.